1919
DOI: 10.1002/bjs.1800072508
|View full text |Cite
|
Sign up to set email alerts
|

The action of chemical and physiological antiseptics in a septic wound

Abstract: SINCE the war began, much attention has been directed t o the treatment of suppurating wounds, for in the earlier years-1914-15-16-practically all the gunshot wounds becanie infected, and even in 1918 nearly all the wounds which were left open for more than a week became grossly infected with pyogenic cocci and other organisms.Prior to the war, the surgeon gave most of his attention to aseptic methods, his great object being to exclude microbes from the wound. The question of how to deal with thc bacteria af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1945
1945
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…In the absence of RBCs, 700 mM H 2 O 2 was effective in destroying all bacteria tested but was only partially effective against C. albicans. However, the microbicidal capacity of 700 mM H 2 Ϫ is a potent microbicidal agent, but it is more effective at destroying host cells, e.g., RBCs, than killing microbes (14,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of RBCs, 700 mM H 2 O 2 was effective in destroying all bacteria tested but was only partially effective against C. albicans. However, the microbicidal capacity of 700 mM H 2 Ϫ is a potent microbicidal agent, but it is more effective at destroying host cells, e.g., RBCs, than killing microbes (14,16).…”
Section: Resultsmentioning
confidence: 99%
“…The reactivities of these agents are indiscriminate and capable of damaging mechanisms of immune defense as well as destroying microbes. Alexander Fleming appreciated this relationship, stating that "leukocytes are more sensitive to the action of chemical antiseptics than are the bacteria, and, in view of this, it is unlikely that any of these antiseptics have the power of penetrating into the tissues and destroying the bacteria without first killing the tissues themselves" (16).…”
mentioning
confidence: 99%
“…Carrel and Dehelly described the successful treatment of various wounds-fresh, phlegmonous, gangrenous, and suppurating-all of which were disinfected and closed within 20 days [24]. Alexander Fleming (1881Fleming ( -1955 noted an initial benefit to the use of topical solutions, such as carbolic acid, perchloride/biniodide of mercury, boric acid, and hydrogen peroxide, but concluded antiseptics had a longer-term negative effect on healing and advised the surgeon to rely ''on his skill alone'' [44]. Although Dakin's solution fell into disfavor after the war, some contemporary surgeons have called for a reevaluation of its potential usefulness [93].…”
Section: Infection and Antibioticsmentioning
confidence: 99%
“…During World War I, Alexander Fleming observed that locally applied antiseptics failed to sterilize chronically infected wounds, but they did reduce the burden of bacteria (Fleming, 1920). In 1939, the instillation of sulfanilamide crystals, along with thorough debridement, hemostasis, primary closure and immobilization, resulted in a reduced infection rate for open fractures (Jensen et al, 1939).…”
Section: Introductionmentioning
confidence: 99%